IMPROVEMENT OF THE BILLING SYSTEM FOR A TELECOMMUNICATION OPERATOR - Kirei, K. O. (Computer Science and Applied Mathematics, 2023)
The article considers one of the directions of charging, accounting, and billing mechanisms of a telecommunications operator, taking into account modern requirements and the development of network technologies. Electronic telecommunications operators (operators) is an organization that provides services for accessing, using, managing in the Internet in Ukraine. Internet access integrates the processes of authorization, authentication and billing of subscribers and must meet certain technical, user and legal requirements. Given that these requirements may change, the organization of access is an actual task. Purpose of research is to improve the Internet access for subscribers of a telecommunications operator, taking into account modern requirements and the development of network technologies. Based on the analysis of technologies for organizing user Internet access technologies that allow organizing Internet access in the context of modern requirements were identified. Based on the analysis of the subject area, relevant technologies and research of existing billing systems, requirements for a software system for monitoring, accounting and Internet access of telecommunications operator subscribers are formed. Empirically, testing and research of the operability of the billing system was performed. The practical significance of the developed system lies in the availability of the necessary functionality for organizing access and billing of subscribers of a telecommunications operator, taking into account modern requirements and the development of network technologies. Scientific novelty consists in the development of an improved algorithm for charging packages of telecommunications operator subscribers and additional features for controlling Internet access. The practical significance of the developed system lies in the availability of the necessary functionality for charging, accounting, and billing mechanisms of a telecommunications operator, taking into account modern requirements and the development of network technologies.